Entertainment computing - ICEC 2012 11th International Conference, ICEC 2012, Bremen, Germany, September 26-29, 2012. Proceedings - Malaka, Rainer; Masuch, Maic; Herrlich, Marc (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 11th International Conference on Entertainment Computing, ICEC 2012, held in Bremen, Germany, in September 2012. The 21 full papers, 13 short papers, 16 posters, 8 demos, 4 workshops, 1 tutorial and 3 doctoral consortium submissions presented were carefully reviewed and selected from 115 submissions. The papers are organized in topical sections on story telling; serious games (learning and training); self and identity, interactive performance; mixed reality and 3D worlds; serious games (health and social); player experience; tools and methods; user interface; demonstrations; industry demonstration; harnessing collective intelligence with games; game development and model-driven software development; mobile gaming, mobile life - interweaving the virtual and the real; exploring the challenges of ethics, privacy and trust in serious gaming; open source software for entertainment.